Wives like us : a novel - Sykes, Plum (Harper, an imprint of HarperCollinsPublishers, 2024)
In The Bottoms, tiny Cotswold villages on the English countryside, filthy rich Tata Hawkins is in a tizzy when her husband runs off with a bikini designer; her glamorous new neighbor, an American divorcée, refuses her overtures at friendship; and her two best friends are distracted by their own problems.